Critical success factors affecting the implementation of halal food management systems: Perspective of halal executives, consultants and auditors - Ahmad, Anis Najiha; Abdul Rahman, Russly; Othman, Mohhidin; Ungku Zainal Abidin, Ungku Fatimah (Elsevier, 2017)
The provision of halal certified food is important for both Muslims consumers as well as halal food manufacturers in Malaysia. Nevertheless, there are still lots of consumers’ complaints resulted from the partial implementation of Malaysia halal standard (MS1500:2009) by these food manufacturers. Hence, critical factors affecting the implementation of halal standard need to be identified and examined as an initial step in fostering its implementation. To date, only limited empirical research is available on the implementation of halal food management system (based on MS1500:2009) especially amongst the small and medium enterprise (SME). Therefore, this study seeks to identify critical factors for effective implementation of halal food management system in SMEs. Using a qualitative approach, fifteen semistructured interviews were carried out with halal executives, consultants and auditors from Malaysian/local halal authority. The recorded interviews were transcribed, translated, coded, and reconciled. Atlas.ti software (version 7) assisted in data coding to identify themes and subthemes. The findings suggested that top management, halal executive, employees, suppliers, and consumers are critical factors. Similarly, information and knowledge, teamwork, support, policy and procedure, and training are also important determinants towards the successful implementation of the systems. Effective recruitment to ensure the availability of Malaysian Muslim manpower, halal personnel empowerment to play dual roles relate to halal and quality/safety, and keeping up to date with recent fatwa development were found to be important and unique to halal context.